Herbart in Kakania (Materiali di Estetica. Terza serie, 2017)
Herbartianism was a sort of official philosophy in the Austro-Hungarian Empire and had a considerable influence on the Austrian culture in the second half of 20th century till the first World War. This influence was greatly promoted by the widespread diffusion of the handbooks written by the Herbartian Lindner, on which Kafka studied as a secondary-school student. The short essay assumes that especially Herbart’s psychology could have been of some importance for Kafka’s work.Keywords: Herbartianism; psychology; educational system